CLIPPERS: chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids. Review of an increasingly recognized entity within the spectrum of inflammatory central nervous system disorders. (4th February 2014) - Dudesek, A.; Rimmele, F.; Tesar, S.; Kolbaske, S.; Rommer, P. S.; Benecke, R.; Zettl, U. K.
Summary Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) is a recently defined inflammatory central nervous system (CNS) disorder, prominently involving the brainstem and in particular the pons. The condition features a combination of clinical symptoms essentially referable to brainstem pathology and a characteristic magnetic resonance imaging (MRI) appearance with punctate and curvilinear gadolinium enhancement 'peppering' the pons. The radiological distribution is focused in the pons and adjacent rhombencephalic structures such as the cerebellar peduncles, cerebellum, medulla and the midbrain. While the lesion burden with a perivascular pattern is typically most dense in these pontine and peripontine regions, enhancing lesions may additionally extend into the spinal cord and supratentorial structures such as the thalamus, basal ganglia, capsula interna, corpus callosum and the cerebral white matter. Another core feature is clinical and radiological responsiveness to glucocorticosteroid (GCS)‐based immunosuppression. As withdrawal of GCS treatment results commonly in disease exacerbation, long‐term immunosuppressive therapy appears to be mandatory for sustained improvement. Diagnosis of CLIPPERS is challenging, and requires careful exclusion of alternative diagnoses. A specific serum or cerebrospinal fluid (CSF) biomarker for the disorder is currently not known. Pathogenesis of CLIPPERS remains poorly understood, and the nosological position of CLIPPERS has still to be established. Whether CLIPPERS represents an independent, actual new disorder or a syndrome that includes aetiologically heterogeneous diseases and/or their prestages remains a debated and not finally clarified issue. Clinicians and radiologists should be aware of this condition and its differential diagnoses, given that CLIPPERS constitutes a treatable condition and that patients may benefit from an early introduction of GCS ensued by long‐term immunosuppression. Based on previous reports in literature – currently encompassing more than 50 reported cases of CLIPPERS – this review addresses clinical features, diagnostic criteria, differential diagnoses and therapeutic management of this peculiar disorder.